Running-induced fatigue and impact loading in runners: A systematic review and meta-analysis - Darch, L.; Chalmers, S.; Wiltshire, J.; Causby, R.; Arnold, J. (Journal of Sports Sciences, 2022)
This systematic review and meta-analysis aimed to synthesise and clarify the effect of running-induced fatigue on impact loading during running. Eight electronic databases were systematically searched until April 2021. Studies that analysed impact loading over the course of a run, in adult runners free of medical conditions were included. Changes in leg stiffness, vertical stiffness, shock attenuation, peak tibial accelerations, peak ground reaction forces (GRF) and loading rates were extracted. Subgroup analyses were conducted depending on whether participants were required to run to exhaustion. Thirty-six studies were included in the review, 25 were included in the meta-analysis. Leg stiffness decreased with running-induced fatigue (SMD -0.31, 95% CI -0.52, -0.08, moderate evidence). Exhaustive and non-exhaustive subgroups were different for peak tibial acceleration (Chi² = 3.79, p = 0.05), with limited evidence from exhaustive subgroups showing an increase in peak tibial acceleration with fatigue. Findings for vertical GRF impact peak and peak braking force were conflicting based on exhaustive and non-exhaustive protocols (Chi² = 3.83, p = 0.05 and Chi² = 5.10, p = 0.02, respectively). Moderate evidence suggests leg stiffness during running decreases with fatigue. Given the non-linear relationship between leg stiffness and running economy, this may have implications for performance.